2009
DOI: 10.1108/17542730910938128
|View full text |Cite
|
Sign up to set email alerts
|

Criteria requirements of the European business excellence model: a suggested approach

Abstract: PurposeThe European Business Excellence Model (EBEM) is nowadays a familiar framework, used for a spectrum of purposes, with the most frequent aim from its full deployment being the attainment of organizational success. The EBEM's requirements, however, involve abstruse management concepts and thus, there is, frequently, a significant variety within the suggested approaches to face the criteria requirements. Although, such integrated business excellence models should not necessarily be of a very prescriptive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Firstly, it was found that there are no known studies related to the motivations leading Portuguese organisations to opt for the EFQM Excellence Model, the tools, approaches or methods to conduct self-assessment. On the other hand, international published studies explore specific case studies of a particular organisation or sector or the conceptual model and no holistic studies about the model in a particular country were found (Antony & Bhattacharyya, 2010;Davies, 2008;Vorria & Bohoris, 2009). Secondly, no one truly knows the organisations' current maturity state, or the tools, approaches or methods used to achieve the desired future maturity state.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, it was found that there are no known studies related to the motivations leading Portuguese organisations to opt for the EFQM Excellence Model, the tools, approaches or methods to conduct self-assessment. On the other hand, international published studies explore specific case studies of a particular organisation or sector or the conceptual model and no holistic studies about the model in a particular country were found (Antony & Bhattacharyya, 2010;Davies, 2008;Vorria & Bohoris, 2009). Secondly, no one truly knows the organisations' current maturity state, or the tools, approaches or methods used to achieve the desired future maturity state.…”
Section: Methodsmentioning
confidence: 99%
“…It is important that public sector organisations work towards the development of these throughout the different organisational levels, so that there can be clarity in the priorities and direction taken and associated behaviour (Ancrum, 2007). Vorria and Bohoris (2009) argue that responsible leaders should align their own ethics and values to the culture of the organisation to ensure that emergent advantages can be sustained.…”
Section: The Criterion Of Leadershipmentioning
confidence: 99%
“…The framework of specific national or regional awards Djerdjouri (2004), Eriksson (2004), Conti (2007), Saunders et al (2008), Vorria and Bohoris (2009) Comparison of different national award models Vokurka et al (2000), Cauchick Miguel (2001), Hui and Chuan (2002), Tan (2002), Khoo and Tan (2003), Kumar (2007), Grigg and Mann (2008), Talwar (2009Talwar ( , 2010 Case studies of companies that adopt a specific award model Eriksson (2003)…”
Section: Topic Referencesmentioning
confidence: 99%